Hubungan Postur Kerja Terhadap Upper Cross Syndrome Pada Penjahit - Puspitasari, Nurwahida; Yusti, Ahadiyah Noppita (Prosiding University Research Colloquium, 2020)
Background: The sewing process is usually done with a static sitting posture for a long time and the bending tailor's body position triggers complaints of musculoskeletal disorders. These complaints cause changes in body shape patterns, functional movements, changes in muscle length and strength between agonists and antagonists, called upper cross syndrome. Objective: The study aims to determine the correlation between work posture and upper cross syndrome in tailors. Method: This research was a quantitative study with descriptive correlation and cross sectional approach. The sample in this study were tailors in four convection companies in Sleman Regency as many as 60 tailors. The sampling in this study used total sampling technique. The work posture assessment instrument was Strain Index and upper cross syndrome was assessed by specific examination of the Janda Cervical Flexion Movement Pattern Test. The data analysis used Chi-Square test. Result: Based on the results of the study, it was found that most of the tailor's work posture had high risk with a strain index value of more than 7 as many as 35 people (58.3%) and the tailors who experienced upper cross syndrome were as many as 42 people (70.0%). The test obtained p-value of 0.000 <0.05 and a contingency coefficient value of 0.531 (moderate correlation closeness). Conclusion: There is a correlation between work posture and upper cross syndrome in tailors.